LINGUISTIC INTERPRETATION AND PRAGMATIC ESSENCE OF THE CATEGORY OF EVALUATION (Universal International Scientific Journal, 2026)
This article analyzes the theoretical foundations of the category of evaluability in linguistics, its objective and subjective aspects, and its place in the structure of connotative meaning. The interpretation of evaluability within the framework of epistemological and pragmatic approaches, the features of the linguistic expression of rational and emotional types of evaluation are highlighted. The relationship between expressiveness, emotionality, imagery, and functional-stylistic components is also considered. The essence of evaluability as a pragmatic category is substantiated based on the views of leading linguists - Sh. Balli, I. V. Arnold, A. V. Kunin, V. N. Teliya, L. A. Sergeeva, and others. The results of the study show that evaluability is an integral part of the semantics of language units.
Keywords: evaluativeness, connotation, subjectivity, pragmatics, expressiveness, emotionality, linguistic evaluation.